(NmASTERSTWO MUZYKANTA(B-(NISPOLNITELQ(B.s (NWYPUSK (B1s ((NmOSKWA s (NSOWETSKIJ KOMPOZITORs, 1972)
(No NEKOTORYH TENDENCIQH RAZWITIQ ISPOLNITELXSKOGO ISKUSSTWA ISPOLNITELXSKOJ KRITIKE I WOSPITANII ISPOLNITELQ(B.s
Keywords: (NmETODIKAs